An Organisational Model for University Libraries in Transition - Savenije, Bas (LIBER Quarterly: The Journal of the Association of European Research Libraries, 2002)
This article describes the tradidional university library organisation, but it also gives an overview of a possible new structure which is in line with the demands described above. It is a flexible structure, in the sense that it can accommodate the present situation, but also the changes that are coming forward and are desirable from a policy as well as a managerial point of view.